Newborn Lipemia Retinalis Resolved with Exchange Transfusion - Rodríguez Vargas, Gabriel (2022)
The purpose of this study was to report the case of a newborn with lipemia retinalis and the clinical evolution after treatment. RetCam fundus photographs were taken before and after treatment with exchange transfusion and fat restriction diet. A 1 month and 25 days old female with a history of 3 days irritability with bilateral leukocoria and a creamy pale blood sample was treated for primary hyperlipidemia. After treatment, symptoms resolved, leukocoria disappeared and fundus exam appearance became normal. Lipemia retinalis in the newborn can fully resolve with appropriate systemic treatment.